Effect of Organic Supplements on Stem Cutting Technique of Kolanut (Cola acuminata) Propagation (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
Kolanut is an important crop with substantial socio-economic values cultivated for their nuts. The major challenges in their propagation are due primarily to prolonged juvenile phase and erratic germination which necessitates needs for efficient and reliable propagation techniques. Improved propagation techniques will increase production, thereby ensuring stable and sufficient supply for both local and international demands. Hence, this study was conducted to evaluate potential of organic supplements to enhance propagation of kolanut through stem cuttings. Treatment consists of organic supplements (Aloe vera leaf, Banana fruit, Moringa leaf and Onion bulb) and water as control, and laid out in a completely randomized design (CRD) replicated three times. Branches 1-2years old, 1-1.5meters long and 2-3cm in diameter obtained from mature and healthy kolanut trees were treated with organic supplement extracts and untreated control. Data were collected on plant vigour, signs of rooting, survival rates and number of active buds, and subjected to analysis of variance (ANOVA). Results revealed that plant vigor was significantly higher for Aloe vera (88.9%), Moringa (88.9%), Banana (80.0%) and Onion (77.8%) compared to water (68.9%). The percentage of rooting was highest in banana (88.9%) > Aloe vera (77.8%) and Moringa (77.8%) > onion (66.7%) and water (60.7%) with lower values. Survival rates were significantly higher in cuttings treated with all extracts (100.0%) compared to water (88.9%). The study concludes that Banana and Aloe vera extracts showed higher efficiency for stem cutting of kolanut, and can therefore be used as supplements for effective vegetative propagation.